Penerapan Media Pembelajaran Explosion Box untuk Meningkatkan Minat Belajar IPA Siswa Sekolah Dasar - Chandra, Shinta Gress; Nisa, Ana Fitrotun; Cahyani, Berliana Henu (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
A boring atmosphere during class is something that students often face. Students seem less interested in participating in learning, especially when teachers teach using conventional methods in the form of lectures. This often becomes a problem for teachers. As a result, the results obtained by students do not match expectations. For this reason, it is necessary to improve learning methods so that it is hoped that they can improve learning outcomes. One way is by using learning media. The aim of this research is to apply the explosion box learning media in an effort to increase students' interest in learning in class VI science lessons at SD Negeri CR so that the learning atmosphere in class is not boring and students can easily understand the material studied in class. This type of research is descriptive qualitative. The research subjects included all sixth grade students at CR State Elementary School, totaling 27 students (7 girls and 20 boys). Data collection techniques use observation and questionnaires. From the results of observations by observers during classroom learning, the final score was 84%. Strengthened by the results of students' independent evaluations using the KKM reference, out of 27 students, 22 students were in learning (81%) and 5 students were incomplete in learning (19%). Meanwhile, the results of calculating the learning interest questionnaire distributed to students showed an average percentage of 80%. Due to the increase in the percentage of completeness of student learning outcomes, it can be concluded that the application of explosion box learning media can increase interest in learning science in class VI students at SD Negeri CR.